(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
Medico legal cases (MLC) are an integral part of medical practice that is frequently encountered by Medical Officers (MO) working in emergency department. An MLC is a case of injury/ illness where the attending doctor, after eliciting history and examining the patient, thinks that some investigation by law enforcement agencies is essential to establish and fix responsibility for the case in accordance with the law of the land. The occurrence of MLCs is on the rise, proper handling and accurate documentation of these cases in casualty is of prime importance to avoid legal complications. This Study profile and pattern of medico-legal cases reported at a tertiary care hospital and suggest measures for improvement of medico-legal work in casualty. This study is a record based retrospective study of medico-legal cases registered in medico-legal register in casualty department of a tertiary care hospital in South Western India. Total number of medico-legal cases reported during 36 months period were 1387, of which majority (n=1125, 81.12%) were males. The most common age group affected was 21-30 years, included 317 (22.86%) cases and second common age group were between 31-40 years, 250 (18.02%) cases. The study revealed that road traffic accidents (n=875, 63.09%) constituted the majority of the medico-legal cases out of total 1387, followed by found dead cases (11.90%). Our study showed that maximum number of medico-legal cases reported to casualty were in month of May (n=198, 14.28%) followed by February (n=157, 11.32 %). Season wise distribution of cases revealed that majority i.e. 40.16% presented during summer season. Majority (n=562, 40.52%) of the incidents took place between 6 pm-12 am i.e. in evening hours. Most of the cases (n=804, 57.97%) reached hospital for examination and treatment within 1 hour after the incident. A need for training of young medical officers in handling medico legal cases was felt so that they are more confident in handling such cases. This will also help in proper documentation and evidence collection in cases of physical and sexual assault.